The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.precisioneng.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Variable stiffness probing systems for micro-coordinate measuring machines

Abstract: Abstract:Micro-scale probing systems are used on specialist micro-coordinate measuring machines to measure small, intricate and fragile components. Probe stiffness is a critical property of micro-scale probing systems; it influences contact force, robustness, ease of manufacture, accuracy and dynamic response. Selecting the optimum stiffness, therefore, represents a significant design challenge, and often leads to undesirable compromises. For example, when contacting fragile surfaces the probe stiffness should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…As well as determining the effect that switching from stiff to flexible mode has on sensitivity, it was also necessary to determine any unwanted stylus tip position offset error. This was determined with the knowledge that the load applied to the beams will result in a deflection of the stylus tip, which is most dominant in the z direction [ 12 ]. If the probing system was not able to return to the same initial zero offset when switched to flexible mode, it would directly impact the probing system error.…”
Section: Suspension Structure Performance Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…As well as determining the effect that switching from stiff to flexible mode has on sensitivity, it was also necessary to determine any unwanted stylus tip position offset error. This was determined with the knowledge that the load applied to the beams will result in a deflection of the stylus tip, which is most dominant in the z direction [ 12 ]. If the probing system was not able to return to the same initial zero offset when switched to flexible mode, it would directly impact the probing system error.…”
Section: Suspension Structure Performance Evaluationmentioning
confidence: 99%
“…Controlling the magnitude of the compressive force, therefore, allows the probe stiffness to be controlled. A full description of the design and working principle behind the variable stiffness probing system is presented elsewhere [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…To prevent the undesirable elastic deformation of the bending stylus impeding the triggering accuracy, the stylus of 5 mm was used. Although using a finite element model (FEM) to study the relationship between applied sensing load and probe stiffness is not within the scope of the study, a trend of using FEM facilities has led to a similar development approach [15]. …”
Section: Mechanism Structurementioning
confidence: 99%
“…Subsequently, our other previous work enhanced both fabrication of micro-styli and multi-directional tactile triggering structure, facilitating the exploration of diverse measurement strategy [13]. Through system advancements, Alblalaihid et al defined an associated measurement strategy for a specific probe [14,15] with stiff and flexible modes. It is observed that such an integral strategy is customized to a developed micro-CMM system while some benchmark parameters associated with the triggering scenarios are affected by the stiffness of a micro-probe, and are transferrable among micro-CMMs.…”
Section: Introductionmentioning
confidence: 99%
“…However, the inertial mass of this microprobe combined with its low stiffness prohibits its integration in a conventional CMM because the low resonance frequency renders movements of the probing system impossible. Previous works include a probing system with a variable stiffness [10], which is able to achieve close to isotropic mechanical behavior (1.3) by using a special suspension structure and applying piezo-electric compressive loads. Furthermore, three-legged suspension structures for low-probing forces have been also investigated [11].…”
Section: Introductionmentioning
confidence: 99%